The association between epicardial adipose tissue thickness and diabetes mellitus, hyperlipidemia, hepatosteatosis, pancreatic steatosis and pancreatitis - Ece Zengin; Aybuke Ucgun; Mehmet Emir Çevik; Sehnaz Evrimler; Ihsaniye Suer Dogan (PLoS ONE, 2026)
Background Epicardial adipose tissue (EAT) is associated with cardiometabolic disorders such as diabetes mellitus (DM), hyperlipidemia, and nonalcoholic fatty liver disease. However, its potential relationship with pancreatic steatosis and pancreatitis remains unclear, and existing studies offer inconsistent findings. Therefore, a clearer understanding of whether EAT reflects broader systemic ectopic fat burden or inflammatory processes is needed.This study evaluated the relationships between EAT thickness and DM, hyperlipidemia, hepatosteatosis, pancreatic steatosis, and pancreatitis. Methods This retrospective, single-center study included 200 patients who underwent abdominal CT between 2022 and 2024. EAT thickness was measured at the mid-RCA and LAD levels, and subcutaneous fat was measured at the umbilical level. Liver and pancreatic steatosis were assessed with CT or MRI. Demographic and clinical data (age, gender, LDL cholesterol, diabetes, and history of pancreatitis) were collected. Mann-Whitney U, Spearman correlation, and logistic regression were used in analyses; p < 0.05 was considered significant. Results Of the 200 patients, 31.4% had diabetes, 42% had hepatosteatosis, and 73.5% had a history of pancreatitis. EAT and subcutaneous fat were significantly higher in women at all levels (p < 0.05). Diabetes was associated with increased EAT in both the RCA (p = 0.002) and the LAD (p = 0.001). In multivariate analysis, RCA-EAT (OR=1.18, p = 0.002) and age (OR=1.03, p = 0.003) were significantly associated with diabetes. High LDL was associated with LAD-EAT (p = 0.030). For pancreatitis, multivariate analysis identified pancreatic steatosis (OR=5.78, p < 0.001) and LAD-EAT (OR=1.52, p = 0.002) as variables significantly associated with a history of pancreatitis. Conclusions EAT thickness is significantly associated with DM, LDL cholesterol, pancreatitis history, and age, supporting its role as a potential imaging biomarker of cardiometabolic risk. These findings suggest that EAT may serve as an imaging marker of broader metabolic and inflammatory burden, supporting its relevance for cardiometabolic risk assessment.